Active surveillance of serious adverse events following transfusion of COVID‐19 convalescent plasma. Issue 1 (22nd October 2021) - Swenson, Erica; Wong, Lisa Kanata; Jhaveri, Perrin; Weng, Yingjie; Kappagoda, Shanthi; Pandey, Suchitra; Pritchard, Angelica; Rogers, Angela; Ruoss, Stephen; Subramanian, Aruna; Shan, Hua; Hollenhorst, Marie
Abstract: Background: The reported incidence of adverse reactions following Coronavirus disease 2019 (COVID‐19) convalescent plasma (CCP) transfusion has generally been lower than expected based on the incidence of transfusion reactions that have been observed in studies of conventional plasma transfusion. This raises the concern for under‐reporting of adverse events in studies of CCP that rely on passive surveillance strategies. Materials and Methods: Our institution implemented a protocol to actively identify possible adverse reactions to CCP transfusion. In addition, we retrospectively reviewed the charts of inpatients who received CCP at Stanford Hospital between May 13, 2020 and January 31, 2021. We determined the incidence of adverse events following CCP transfusion. Results: A total of 49 patients received CCP. Seven patients (14%) had an increased supplemental oxygen requirement within 4 h of transfusion completion, including one patient who was intubated during the transfusion. An additional 11 patients (total of 18, 37%) had increased oxygen requirements within 24 h of transfusion, including 3 patients who were intubated. Six patients (12%) fulfilled criteria for transfusion‐associated circulatory overload (TACO). Conclusion: Using an active surveillance strategy, we commonly observed adverse events following the transfusion of CCP to hospitalized patients. It was not possible to definitively determine whether or not these adverse events are related to CCP transfusion. TACO was likely over‐diagnosed given overlap with the manifestations of COVID‐19. Nevertheless, these results suggest that the potential adverse effects of CCP transfusion may be underestimated by reports from passive surveillance studies.